The Role And Responsibilities Of A Notary In Providing Legal Understanding To The Public In Relation To The Preparation Of Notarial Deeds (Study At A Notary Office In Malang) - Nurjanah, Nurjanah; Sunardi, Sunardi (International Significance of Notary, 2025)
Abstract : The aim of this research is to find out and examine the public's understanding of notarial deeds and their functions; the role and responsibilities of notaries in providing legal understanding to the public regarding the making of notarial deeds; as well as what obstacles are experienced by notaries and efforts to overcome obstacles in providing legal understanding to the public regarding the making of notarial deeds. This research is a type of sociological juridical research, which in other words is a type of sociological legal research and can also be called field research, namely examining applicable legal provisions and what is happening in reality in society or in other words, namely research conducted on actual conditions. or real situations that occur in society with the aim of knowing and finding the facts and data needed, after the required data is collected it then leads to problem identification which ultimately leads to solving the problem. This research is included in empirical research, because it wants to know the role of notaries in providing understanding of society's law. The results of this research are (1) the role and responsibilities of notaries in providing legal understanding to the public in relation to making notarial deeds, carried out by providing legal advice to their clients in accordance with article 15 paragraph (2) letter e UUJN. (2)The obstacles experienced by notaries in providing legal understanding to the public in relation to making notarial deeds include the low level of basic education in the community, lack of legal knowledge among the community, and distrust of the legal process. People often have difficulty understanding the legal terminology and procedures required to make a notarial deed, and do not understand the importance of notarial deeds in protecting their rights and providing legal certainty (3). Meanwhile, efforts to overcome obstacles are through counseling by notaries in villages, schools and places of worship, as well as improving clear and effective communication, are important steps to clarify complex legal concepts for society. Regular training and seminars also support the professionalism of notaries in carrying out their duties well. Through collaboration with the Indonesian Notary Association (INI)..